A Capacity Market for Electricity Sectors with Promotion of Renewable Energy - Sebastian Schäfer; Lisa Schulten (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
A capacity mechanism next to the energy-only market provides necessary investment incentives that spot markets lack. The adequate capacity mix can only be achieved by accounting for the current transition phase to electricity generation with a growing share of renewables. We show that an increasing share of renewable energy leads to a comparative advantage for peak-load power plants in a capacity market. This results in higher flexibility as opposed to missing flexibility induced by the merit order effect at the spot market. Suggested capacity mechanisms do not account for the promotion of renewable energy so far. We consider support for renewables via endogenous discrimination of prices paid for offered capacity. This triggers more efficient incentives to direct the capacity mix to its long-run equilibrium where discriminated prices converge to one equilibrium capacity price.
Keywords: Q41; Q42; Q48; L94; 330; Capacity Markets; Electricity Markets; Resource Adequacy; Reliability Options; Renewable Energy; Merit Order Effect